Vagotomy changes calcium eflux in pancreatic islets - Silva, Carlos Alberto; Pardi, Adriano C. R.; Arruda, Eder J.; Grassi, Daniel O.; Severi, Maria T. M.; Gonçalves, Antonio A. (Medicina (Ribeirao Preto), 2009)
The participation of the parasympathetic nervous system in insulin secretion modulation is clearly evident during the cephalic phase that follows the sensorial stimulus provoked by food in the mouth. The objective of this study was to evaluate if selective subdiaphragmatic vagotomy of the pancreatic branch could alter 45Ca2+ permeability in the plasmatic membrane of pancreatic cell. To assess the effects of vagotomy, we used glucose and the potentializer carbamylcholine on the glucose effects. Analysis of 45Ca2+ efflux was accomplished in isolated islets by digestion with collagenase and perfused with KREBS and carbamylcholine in rats from groups control and denervaded. After 15 and 30 days of the pancreatic branch vagotomy, the isolated islets did not respond to a glucose stimulus of 16,7 mM and also presented alteration in carbamylcholine sensibility (CCh 100μm) when added to the solution containing 5,6 mM of glucose. Our results suggest that the vagus nerve (pancreatic branch) contributes with regulation of insulin secretory process of pancreatic β cells. This effect could be associated to the modulation of responses induced by glucose and the regulation of acetylcholine, a neurotransmitter modulator of insulin secretion.